UNIVERSITY AUTONOMY FOR SUSTAINABLE DEVELOPMENT: RESULTS OF THE TIMES HIGHER EDUCATION IMPACT RANKINGS 2022 - Riabchenko, Volodymyr; Bulvinska, Oksana (Continuing Professional Education: Theory and Practice, 2022)
The article is devoted to the study of the results of the Times Higher Education Impact Rankings 2022, which reflects the activities of universities in ensuring the sustainable development. It is emphasized that the autonomy of universities, along with the possibilities of governance and academic freedom, strengthens their social responsibility for the results of their activities in achieving the goals of sustainable development. One of the mechanisms for evaluating the contribution of universities to ensuring sustainable development is the Times Higher Education Impact Rankings, participation in which is voluntary for higher education institutions. The article analyzes the methodology of the ranking, notes its strengths and gaps. The positive sides of the methodology are openness for universities to be widely involved in the ranking on a voluntary basis, the opportunity for universities to expand their contribution to solving social, political, ecological, economic issues in their country and around the world; certain flexibility of the criteria allows to compare a very diverse environment of higher education institutions. Gaps in the methodology of the Times Higher Education Impact Rankings include the optional participation of universities in the ranking, which leads to the absence of most universities in the world, in particular those that are top according to other rankings; a certain imbalance in the weighting factors of the ranking criteria, the impossibility of longitudinal analysis of university achievements. It was emphasized that a statistical study of the results of the Times Higher Education Impact Rankings 2022 testified to the high achievements of universities from Europe, Australia, and North America, as well as an increase in the ranking of the share of higher education institutions from developing regions.